2022
DOI: 10.1093/neuonc/noac003
|View full text |Cite
|
Sign up to set email alerts
|

IDH-mutated gliomas promote epileptogenesis through d-2-hydroxyglutarate-dependent mTOR hyperactivation

Abstract: Background Uncontrolled seizures in patients with gliomas have a significant impact on quality of life and morbidity, yet the mechanisms through which these tumors cause seizures remain unknown. Here, we hypothesize that the active metabolite D-2-hydroxyglutarate (D-2-HG) produced by the IDH-mutant enzyme leads to metabolic disruptions in surrounding cortical neurons that consequently promote seizures. Methods We use a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Mice bearing mutant IDH1 tumours showed a significant increase in their survival following treatment with D2-HGDH-OE CAR-T cells. It was later shown that the mechanism behind this was down to the reduction in D2-HG, and therefore the removal of immune suppression, allowing for an increase in memory cell differentiation and cytokine production [77].…”
Section: Idh Mutation and Tumour-specific Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice bearing mutant IDH1 tumours showed a significant increase in their survival following treatment with D2-HGDH-OE CAR-T cells. It was later shown that the mechanism behind this was down to the reduction in D2-HG, and therefore the removal of immune suppression, allowing for an increase in memory cell differentiation and cytokine production [77].…”
Section: Idh Mutation and Tumour-specific Immune Cellsmentioning
confidence: 99%
“…Indeed, it has been demonstrated that activation of NMDA receptors, whether by glutamate or D2-HG, leads to an increase in membrane excitation and thus, epilepsy [93] [94]. The epileptogenic activity elicit by IDH mutation on the neighboring neurons has been recently demonstrated to be triggered by the mTOR pathway and it can be blocked by the addition of rapamycin [77]. However, the concentrations of extracellular D2-HG produced by mutant IDH can reach the mM range [95], whilst the normal extracellular concentration of glutamate is estimated to be between the nM and µM range [96].…”
Section: Idh Mutation and Tumour-associated Epilepsymentioning
confidence: 99%
“…Several important clinically relevant factors contributing to epileptogenesis (i.e. the development and extension of brain tissue capable of generating spontaneous recurrent seizures) in brain tumors have been identified, including IDH-mutation and its active metabolite d -2-hydroxyglutarate [ 8 , 9 ], and BRAF V600E mutation (especially in gangliogliomas) [ 10 ▪ , 11 ▪▪ ].…”
Section: Epidemiology and Epileptogenesismentioning
confidence: 99%
“…These mutations, however, are not decisive for the development of epilepsy, as IDH1 and IDH2 mutations do increase the risk of developing seizures in gliomas [ 51 , 52 , 53 , 54 ], while LEATs typically lack IDH1 or IDH2 mutations and 1p/19q co-deletions [ 11 , 40 , 41 , 42 ]. Moreover, recent data suggest that the mTOR pathway hyperactivation by d-2-HG is a potential mechanism of epileptogenesis in patients with IDH-mutated gliomas [ 3 , 55 , 56 ].…”
Section: Known Risk Factors For Tumor Epileptogenesismentioning
confidence: 99%